Development of Educational Augmented Reality Game as English Language Learning Media with Character Education Values - Elinda Umisara; Alim Mutaqin; Siti Ulin Nuril Hidayah (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
The primary objective of this research is to create an educational Augmented Reality game as a learning tool. This media can be accessed on Android smartphones and developed using the Unity application. The study adopts a research and development (R&D) approach, following the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The validation process involves assessments by subject matter experts, media experts, and language experts, resulting in a highly favorable rating with a validity percentage of 96.33 percent for the learning media. To conduct the testing, 15 fifth-grade Elementary School students are selected using purposive sampling. The students’ responses to the educational game, focusing on the English language topic